Effective Exercises Revolutionize Neck Health by Combating Forward Head Posture: Latihan yang Efektif Merevolusi Kesehatan Leher dengan Memerangi Postur Kepala ke Depan - Arya samudra ramadhani Arya; Widi Arti; Bagas Anjasmara (Academia Open, 2024)
This study investigated the effectiveness of deep cervical flexor exercise and neck callet exercise in improving neck functionality among university students with forward head posture. Through a quasi-experimental design, both exercises were implemented three times per week for four weeks, with neck functionality assessed using the Neck Disability Index. Results revealed significant improvements in both groups post-intervention, with mean pre-test scores decreasing from 38.166 to 31.500 for deep cervical flexor exercise and from 37.333 to 31.166 for neck callet exercise. A significant difference was observed between the two groups. These findings highlight the efficacy of targeted exercises in enhancing neck functionality and addressing the negative impacts of forward head posture associated with prolonged gadget use. Highlight: Improved neck function after targeted exercises in university students. Both exercises effective for addressing forward head posture. Quasi-experimental design supports efficacy of targeted exercises. Keyword: Neck functionality, Forward head posture, Exercise intervention, University students, Quasi-experimental design